Sposoby radzenia sobie ze stresem a motywacja do działania członków studenckich kół naukowych - Wiktoria Krakowiak (Studia Paradyskie)
The development of modern society undoubtedly affects the behavior and well-being of an individual. Concepts such as stress and motivation are the subject of numerous discourses. Students who are members of Scientific Clubs are also exposed to stress resulting not only from the fact of studying, but also from the activities undertaken as part of the activities of the Club to which they belong. The degree of students' involvement in the work of scientific groups certainly depends on their motivation. The work shows the relationships between the ways of coping with stress and the motivation to act among members of Student Scientific Clubs. The aim of the study was to attempt to determine the relationship between the ways of coping with stress and the motivation to act among members of student scientific clubs.